Design, synthesis, pharmacological characterization of a fluorescent agonist of the P2Y14 receptor. Issue 21 (1st November 2015) - Kiselev, Evgeny; Balasubramanian, Ramachandran; Uliassi, Elisa; Brown, Kyle A.; Trujillo, Kevin; Katritch, Vsevolod; Hammes, Eva; Stevens, Raymond C.; Harden, T. Kendall; Jacobson, Kenneth A.
Graphical abstract